Disaster Media: Bending the Curve of Ecological Disruption and Moving toward Social Justice - Lisa Parks; Janet Walker (Media + Environment)
This essay introduces a special stream of *Media+Environment* focused on “disaster media.” In the process, the authors conceptualize this term in relation to “natural” and other disasters, including the COVID-19 pandemic, and explore how understandings of “disaster media” are embedded within several areas of humanities-based film and media scholarship. Writing from the social ecological premise that consequences of disasters stem in large part from systemic actions, the introduction develops three general arguments about disaster media as an analytic. First, disasters cause people to rethink what “media” are and to contend with the fact that, especially during disasters, media are constantly changing and being updated; they also escape the screen and sculpt the environment (media are not only representational but also affective and infrastructural). Second, because they come to the fore in relation to crisis situations, disaster media help expose structural inequalities; practices of relief and reform need to happen and can be facilitated (or inhibited) by mediatic means. Finally, disaster media need to be considered in relation to the multiple temporalities of climate disruption (from the *longue durée* of glacial flow to uncertain and sudden extreme weather). Discussing these issues, the authors also introduce pieces in the stream that are focused on humanitarian drone interventions and glacier-melt artworks.